Exploring consumer perceived risk and purchase intention of water-saving appliances: A moderated dual-mediation model - Wang, Teng; Tian, Ming (Frontiers in Psychology, 2023)
With the blooming of the socio-economy in China, urban water consumption continues rising, and the promotion of water-saving appliances has become one of the priorities of water saving efforts. Based on the perceived risk theory, this research constructs a moderated mediation model to explore the mechanisms that explain and affect consumers' willingness to purchase water-saving appliances. The study finds that consumers' perceived risk of buying water-saving appliances is mainly functional, economic, and psychological risks. Perceived risk will reduce consumers' quality trust and green trust in water-saving appliances, and indirectly influences consumers' willingness to buy through quality and green trust. In addition, we find that consumer knowledge of water-saving appliances can weaken the negative impact of perceived risk on quality trust and green trust and the indirect inhibitory effect on purchase intentions. In final, we provide policy recommendations to guide consumers to purchase water-saving appliances and promote the popularization of water-saving appliances.